Clinical and epidemiological characterization of a lymphogranuloma venereum outbreak in Madrid, Spain: co‐circulation of two variants. (4th June 2013) - Rodríguez‐Domínguez, M.; Puerta, T.; Menéndez, B.; González‐Alba, J. M.; Rodríguez, C.; Hellín, T.; Vera, M.; González‐Sainz, F. J.; Clavo, P.; Villa, M.; Cantón, R.; Del Romero, J.; et al.
Abstract The lymphogranuloma venereum (LGV) outbreak described in the Netherlands in 2003, increased the interest in the genotyping of Chlamydia trachomatis. Although international surveillance programmes were implemented, these studies slowly decreased in the following years. Now data have revealed a new accumulation of LGV cases in those European countries with extended surveillance programmes. Between March 2009 and November 2011, a study was carried out to detect LGV cases in Madrid. The study was based on screening of C. trachomatis using commercial kits, followed by real‐time pmpH‐PCR discriminating LGV strains, and finally ompA gene was sequenced for phylogenetic reconstruction. Ninety‐four LGV infections were identified. The number of cases increased from 10 to 30 and then to 54 during 2009–2011. Incidence of LGV was strongly associated with men who have sex with men; but in 2011, LGV cases were described in women and heterosexual men. Sixty‐nine patients were also human immunodeficiency virus (HIV) positive, with detectable viral loads at the moment of LGV diagnosis, suggesting a high‐risk of co‐transmission. In fact, in four patients the diagnosis of HIV was simultaneous with LGV infection. The conventional treatment with doxycycline was prescribed in 75 patients, although in three patients the treatment failed. The sequencing of the ompA gene permitted identification of two independent transmission nodes. One constituted by 25 sequences identical to the L2b variant, and a second node including 37 sequences identical to L2. This epidemiological situation characterized by the co‐circulation of two LGV variants has not been previously described, reinforcing the need for screening and genotyping of LGV strains.